2007
DOI: 10.1103/physrevlett.99.057201
|View full text |Cite
|
Sign up to set email alerts
|

Hysteretic Behavior of Angular Dependence of Exchange Bias inFeNi/FeMnBilayers

Abstract: For FeNi/FeMn bilayers, the angular dependence of exchange bias shows hysteresis between clockwise and counterclockwise rotations, as a new signature. The hysteresis decreases for thick antiferromagnet layers. Calculations have clearly shown that the orientation of antiferromagnet spins also exhibits hysteresis between clockwise and counterclockwise rotations. This furnishes an interpretation of the macroscopic behavior of the ferromagnetic layer in terms of the thermally driven evolution of the magnetic state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 27 publications
4
25
0
2
Order By: Relevance
“…In general, rotation processes are more relevant in one branch of the hysteresis loop, in which a larger density of domains during irreversible domain nucleation processes is also observed. 25,28,29,35,36 For some systems, rounded transitions in M ʈ and larger M Ќ values are found in the descending branch, 20,21,[25][26][27][28][34][35][36] where the field is applied parallel to the exchange-bias direction, while other systems display the opposite behavior. [21][22][23][24][25][29][30][31][32][33] Our results indicate that this discrepancy is related to the difference between a collinear and a noncollinear anisotropy case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, rotation processes are more relevant in one branch of the hysteresis loop, in which a larger density of domains during irreversible domain nucleation processes is also observed. 25,28,29,35,36 For some systems, rounded transitions in M ʈ and larger M Ќ values are found in the descending branch, 20,21,[25][26][27][28][34][35][36] where the field is applied parallel to the exchange-bias direction, while other systems display the opposite behavior. [21][22][23][24][25][29][30][31][32][33] Our results indicate that this discrepancy is related to the difference between a collinear and a noncollinear anisotropy case.…”
Section: Resultsmentioning
confidence: 99%
“…Asymmetries in the magnetization reversal have been observed for many FM/AFM systems with both in-plane [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and perpendicular 35,36 anisotropy for the FM layer. In general, rotation processes are more relevant in one branch of the hysteresis loop, in which a larger density of domains during irreversible domain nucleation processes is also observed.…”
Section: Resultsmentioning
confidence: 99%
“…And the crystalline degree of AFM layer has close connection with anisotropy energy barrier which will increase with the improving of the AFM crystalline degree. So the worse IrMn crystalline degree does not increase the anisotropy energy barrier but decrease it, which will facilitate the pinning direction inclines to unstable state [18].…”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, some properties of these systems are not well explained. Gao et al found that the coercivity of a FM/AFM coupling system increases with the AFM layer thickness first, and decreases after a peak, and then tends to saturate. This kind of peak in the coercivity curve has also been reported by other authors and its origin is currently not satisfactorily explained.…”
Section: Introductionmentioning
confidence: 99%